Folding of Polypeptide Chains in Proteins: A Proposed Mechanism for Folding - Lewis, Peter N. (1971)
A mechanism is proposed for the folding of protein chains. On the basis of short-range interactions, certain aminoacid sequences have a high propensity to be, say, α-helical. However, these short helical (or other ordered) regions can be stabilized only by long-range interactions arising from the proximity of two such ordered regions. These regions are brought near each other by the directing influence of certain other aminoacid sequences that have a high probability of forming β-bends or variants thereof, also on the basis of short-range interactions. An analysis is made of the tendency of various amino acids to occur in β-bends, and it is possible to predict the regions of a chain in which a β-bend will occur with a high degree of reliability.